Dinamiche di purificazione e abilitazione rituale nell’Inno omerico a Apollo - Colangelo, Eleonora (O T I V M, 2017)
Considering synesthesia as a key factor in the Greek experience of miasma, the performance appears to be subject to the hagnizein process. Therefore, even for the construction of a scenic and performative space there would exist a „regulation of pure‟, based to hagneia canons. In turn, the same regulation is directed to validate the rhapsodic practice itself. This had to be the case of the Homeric Hymn to Apollo (HHA). The purpose of this paper is to enlighten exactly the micro-history of the HHA monumental unification, signed by cathartic prescription and mimetic representation. In fact, a direct connection binds the prescriptive sections in HHA (vv. 532-43) to some hexametrical cathartic programmata (including LLS 108, 115, 191). In particular, the analysis of some purificatory oracles from Didyma and Tralleis (e.g. SGO 1.01.19.01) will allow us to reconsider Certamen Homeri et Hesiodi, ll. 319-22 and the schol. Pind., N. 2.1c, as primary sources for HHA paradosis.